Prevalence of periodontal pathogens in Brazilians with aggressive or chronic periodontitis - Cortelli, Jose R.; Cortelli, Sheila Cavalca; Jordan, Shawn; Haraszthy, V. I.; Zambon, J. J. (Journal of clinical periodontology, 2005)
Objectives: Previous studies suggest differences between geographically and racially distinct populations in the prevalence of periodontopathic bacteria as well as greater periodontal destruction associated with infection by highly leucotoxic Actinobacillus actinomycetemcomitans. The present study examined these hypotheses in Brazilians with aggressive or chronic periodontitis. Materials and Methods: Clinical, radiographical, and microbiological assessments were performed on 25 aggressive periodontitis and 178 chronic periodontitis patients including 71 males and 132 females, 15–69 years of age. Results: The prevalence of Porphyromonas gingivalis was similar to that of other South American populations. The prevalence of A. actinomycetemcomitans and its highly leucotoxic subgroup was higher in Brazilians. Highly leucotoxic A. actinomycetemcomitans was more prevalent in aggressive periodontitis (χ2=27.83) and positively associated with deep pockets (>6 mm, χ2=18.26) and young age (<29 years, χ2=18.68). Greater mean attachment loss was found in subjects with highly leucotoxic A. actinomycetemcomitans than in subjects with minimally leucotoxic (p=0.0029) or subjects not infected (p=0.0001). Conclusion: These data support the hypothesis of differences between populations in the prevalence of periodontopathic bacteria and of greater attachment loss in sites infected with highly leucotoxic A. actinomycetemcomitans. Detection of highly leucotoxic A. actinomycetemcomitans in children and adolescents may be a useful marker for aggressive periodontitis.